Chapter L'impatto del progetto TECO-D Pedagogia sul CdS in Scienze dell'Educazione e della Formazione L-19 dell'Università degli studi di Firenze - Silva, Clara Maria (Studies on Adult Learning and Education, 2022)
The paper illustrates the application of the national experiment, promoted by ANVUR, and called TECO, to the Bachelor of Science in Education and Training at the University of Florence. The analysis developed in the article emphasizes how this application has effects on the overall architecture of the bachelor course to support the provision of a solid and quality education, based on professional knowledge and skills, but also on individual components of the course and on the learning outcomes.